Quaid-i-Azam's Role in South Asian Political Crisis, 1921-1924 - Riaz Ahmad, Dr. (Rawalpindi, Pakistan Alvi Publishers, 1989)
Mohammed Ali Jinnah, 1876-1948, statesman and founder of Pakistan.
Include Abbreviations, Bibliography and Index.
Keywords: India -- Politics and government -- Jinnah, Mahomed Ali, 1876-1948